British Writer Carl Eric Bechhofer Roberts About Batumi - Nikoleishvili, Otar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2020)
One of the most important parts of the history of Batumi and Adjara, in general, is the period of the Democratic Republic of Georgia. Batumi, as one of the main ports on the Black Sea, because of its military and trade-economic importance and geopolitically strategic location, was always under the special attention of the hegemonic states of the world. Due to all the above, along with Georgian, there are several highly interesting historical sources about Batumi and Adjara, which further enrich the history of the above-mentioned city and region, as well as the relevant period of our country in general. One such source of foreign writing is the book “A Wanderer’s Log: Being Some Memories of Travel in India, the Far East, Russia, the Mediterranean & Elsewhere,” by British lawyer, journalist, and writer Carl Eric Bechhofer Roberts. The abovementioned book was published in 1922 in London. It focuses on many interesting issues from the time of the Democratic Republic of Georgia, including the British presence in Batumi and its impressions at the time. It is noteworthy that Carl Roberts paid special attention to Russia and the Caucasus region, as evidenced by the fact that in addition to the above-mentioned book, he has published several other works devoted to these issues. In 1919, he visited our country.